DIGITAL ETHICS: THE DARK SIDE OF SOCIAL MEDIA ALGORITHMS - Polyzos, Dimitris; Koliatsas, Ilias (Open Schools Journal for Open Science, 2025)
Social media algorithms (SMAs) have become an inseparable part of the online experience, shaping what users see, how they interact, and even what they believe. While these algorithms are designed to enhance personalization and increase user engagement, they also pose significant ethical challenges. They influence mental health, reinforce echo chambers, and contribute to the spread of misinformation. In addition, they raise serious concerns about privacy, data collection, and manipulation, particularly among young and vulnerable users. This presentation aims to examine the darker implications of SMAs and proposes ways to implement ethical frameworks and regulations that promote responsible algorithm design and use.